Neuropsychological evidence for visual- and motor-based affordance: effects of reference frame and object-hand congruence. - Humphreys, G; Wulff, M; Yoon, E; Riddoch, M (2010)
Two experiments are reported that use patients with visual extinction to examine how visual attention is influenced by action information in images. In Experiment 1 patients saw images of objects that were either correctly or incorrectly colocated for action, with the objects held by hands that were congruent or incongruent with those used premorbidly by the patients. The images were also shown from a 1st- and 3rd-person perspective. There was an overall reduction in extinction for objects colocated for action. In addition, there was an extra benefit when the objects were held in hands congruent with those used by the patients and when the objects were seen from a 1st-person perspective. This last result fits with an effect of motor simulation, over and above a purely visual effect based on positioning objects correctly for action. Experiment 2 showed that effects of hand congruence could emerge with images depicted from a 3rd-person perspective when patients saw themselves holding the objects. The data indicate 2 effects of action information on extinction: (a) an effect of colocating objects for action, which does not depend on a self-reference frame (a visual effect), and (b) an effect sensitive to object-hand congruence, which does depend on a self-reference frame (a motor-based effect). The self-reference frame is induced when stimuli are viewed from a 1st-person perspective and when an image of the self is seen from a 3rd-person perspective. Both visual and motor-based effects of action information facilitate the spread of attention across objects.